Groundwater and underground excavations: From theory to practice - Sharifzadeh, Mostafa; Javadi, M. (2017)
© 2017 Taylor & Francis Group, London, UK. The hydraulic behavior and associated mechanical, physical, and chemical processes of geological formations and rock masses are one of the most important aspects of rock engineering applications, especially for underground excavations. Although the existence of groundwater around underground excavations presents advantageous engineering applications such as hydrocarbon or compressed air storages in unlined rock caverns (Javadi et al., 2014a, 2016b; Froise, 1987; Lee & Song, 2003; Yoshida et al., 2013), most underground excavations usually face different kinds of direct and indirect groundwater challenges (ITA, 1991; Tseng et al., 2001; Yang et al., 2009; Yoo et al., 2012; Gattinoni et al., 2013; Zarei et al., 2012). From the engineering point of view, these groundwater challenges can be categorized into four major groups including in-tunnel (mainly due to the groundwater inflow and construction problems), near zone around tunnel (i.e. instability, collapse, swelling), far zone around tunnel (mainly groundwater alteration and drawdown), and support system(i.e. deterioration, erosion) challenges that result in increasing time, cost, risk, and environmental hazards and decrease the safety and work efficiency. Successful and appropriate treatment of these challenges requires a problem statement and thorough understanding of the effective features. The groundwater reaction linked to underground excavations is a result of complex interactions between effective features such as regional hydrology, geological structure, and flow paths that vary from mega to micro-scales. The regional hydrology incorporation with geological conditions mainly control the local hydrogeological conditions of host ground of underground excavations. There is a very close interrelationship between the local hydrogeological conditions and geological structures (Milanovic, 1985; Elhag & Elzien, 2013; Bense et al., 2003; Saul Caine et al., 1996) where some geological structures such as faults may change the groundwater state and anisotropy of rock mass permeability. On the other hand, the groundwater itself can influence the mechanical, physical, and chemical properties of rock mass (Sharifzadeh et al., 2002; Masuda, 2001; Vásárhelyi & Ván, 2006; Brantley et al., 2008), which is called waterrock interaction. Therefore, the realistic analysis of groundwater processes linked with underground excavations should be performed through a framework that briefly reflects the effect of geological structures, rock mass hydraulic behavior, and waterrock interactions. In this case, the conceptual models and classification systems, which present an overview of interactive phenomena, can be utilized to gain an improved understanding and identify the different types of dominant groundwater processes linked to underground excavations. Fromthemodeling point of view, the rock mass condition and its hydraulic behavior can be considered as the main controlling features of groundwater processes around underground excavations. In many geological formations, the matrix permeability is negligible compared to permeability of fractures and the bulk of fluid flowtakes place along preferred flow paths or channels within the fractures (Javadi & Sharifzadeh, 2011; Hitchmough et al., 2007; Odling et al., 1999) as field experiments provide indirect evidence of these preferential pathways (Hsieh & Neuman, 1985; Neuman & Depner, 1988; Novakowski & Bickerton, 1997; Nativ et al., 1999;Wang et al., 1999). In such situations, the hydraulic behavior of rock mass is mainly governed by fractures and their interconnectivity. Generally, the fluid flow processes through rock masses can be investigated by application of continuum and discontinuum modeling methods. The main difference between these methods is mainly referred to as the implementation of fractures effect that is considered implicitly and explicitly in the discontinuum modeling methods, respectively (Javadi et al., 2016a). Proper application of these methods depends on different factors including the heterogeneity intensity of rock mass, geometrical characteristics of fractures, study objects, and the scale of dominant processes relative to underground excavation. It is worth noting that all geological formations, even the ones that are homogeneous, show random variations (spatial nonuniformity) in the values of the hydrogeological parameters (Freeze, 1975) and consequently, there is a considerable amount of uncertainty in the characterizing of the properties of the subsurface rock masses (Renard, 2007). Therefore, it is becoming essential to be able to characterize the uncertainty of groundwater processes and rock mass hydraulic behavior. This can be achieved through implementation of stochastic hydrogeology (Dagan, 2002, 2004; Neuman, 2004; Renard, 2007; Hu et al., 2004; Winter, 2004; Javadi et al., 2016a) that deals with stochastic methods to describe and analyze groundwater processes in both continuum and discontinuum models. This chapter deals with the link between groundwater processes in geological formation around underground excavations. The main purpose of this chapter is to show the present state of knowledge on the theoretical to practical issues related to hydraulic behavior of geological formation and its effects on the underground excavations. To reach this goal, an overview of the governing equations of groundwater flow in geological formation and its modeling methods is firstly described based on the theoretical framework of rock engineering. Then, the interaction between groundwater and underground excavations is presented mainly in terms of water-rock interaction and challenges that are practically experienced in different projects. Finally, the prediction of groundwater inflow to underground excavations is discussed by focusing on effective features, the role of geological structures, and suitable analysis method.